An assessment on seasonal analysis of wind energy characteristics and wind turbine characteristics - Akpinar, EK; Akpinar, S (Pergamon-Elsevier Science Ltd, 2005)
This paper presents seasonal variations of the wind characteristics and wind turbine characteristics in the regions around Elazig, namely Maden, Agin and Keban. Mean wind speed data in measured hourly time series format is statistically analyzed for the six year period 1998-2003. The probability density distributions are derived from the time series data and their distributional parameters are identified. Two probability density functions are fitted to the measured probability distributions on a seasonal basis. The wind energy characteristics of all the regions is studied based on the Weibull and Rayleigh distributions. Energy calculations and capacity factors for the wind turbine characteristics were determined for wind machines of different sizes between 300 and 2300kW. It was found that Maden is the best region, among the regions analyzed, for wind characteristics and wind turbine characteristics. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Weibull and Rayleigh distributions; wind speed data; wind energy